Design and simulation of air flow inside double wall infant incubator by using 3D FEM; Case study for multi inflow and outflow slot - A. Wongkamhang (2018)
This paper presents a concept of the design and development of an infant incubator by increasing a number of an air flow slot for air-inlet and air-outlet inside a double wall infant incubator. The number of airflow inlet slot is increase to 2 while an airflow outlet slot is to 4 at the lateral side. The study is done by using FEM simulation to compare between single air flow slot and multi air flow slot. The simulation results show that air temperature in multi-slot provides more distribution that the single wall obviously and no air layer exist in the air hood. In term of rising temperature, 4 temperature monitoring points was located around an infant area then be averaged during simulation process, multi-slot show a shorter time than single-slot to reach a setting temperature at 35 C. These simulations provides a useful basic information to prepare a real validation in the near future. © 2013 IEEE.